GUARDIANS OF SACRED GLASS BOWL: WOMEN AND CONCEPT OF CHASTITY WITH REFERENCE TO MALAYALAM NOVELS CHEMMEEN, RATHI NIRVEDAM, SUGANDI ENNA AANDAAL DEVANAYAKI AND KHASAKKINTE ITHIHAASAM
Chastity and Virginity have restricted their meaning on gender basis and these words have come to be used only in relation with women. This hackneyed notion has crossed all linguistic, cultural, communal and religious boundaries and is harbored by all male dominated society. No myth is there to protect the chastity of men, only female sexuality is ‘sheltered’ by these virginity/chastity myths, definitely a construction of androcentric culture, and often powerless women become a prey to so called protectionism. Women are trained to internalize the double standard of morality for men and women by the constant interference of media, family, society, religious organizations and other all that are driven craze by this virginity fetish.